2021
DOI: 10.1093/nop/npab011
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of stereotactic radiosurgery for large vestibular schwannomas: a systematic review and meta-analysis

Abstract: Background Large vestibular schwannomas (VS) pose a treatment challenge for both microsurgery (MS) and stereotactic radiosurgery (SRS). Technical developments have allowed for safer irradiation of large tumors. It remains unclear if SRS can achieve appropriate tumor control and acceptable cranial nerve toxicities. In this study, we assess outcomes of irradiation for large VS. Methods PubMed MEDLINE, EMBASE, Web of Science, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Previously published GKRS and SRT experiences have shown excellent tumor control rates (84-100%), exceptional facial nerve function preservation (100% in ve series), cochlear nerve preservation (33-100%), and low treatment failure rates (0-12%) [6]. A recent systematic review and meta-analysis of the outcomes of SRS for large VSs revealed that 89% of patients achieved clinical control and 92% achieved radiographic control, with a 7% salvage surgery rate [52]. Con rming these ndings, all patients retained serviceable hearing and no facial nerve dysfunction was identi ed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Previously published GKRS and SRT experiences have shown excellent tumor control rates (84-100%), exceptional facial nerve function preservation (100% in ve series), cochlear nerve preservation (33-100%), and low treatment failure rates (0-12%) [6]. A recent systematic review and meta-analysis of the outcomes of SRS for large VSs revealed that 89% of patients achieved clinical control and 92% achieved radiographic control, with a 7% salvage surgery rate [52]. Con rming these ndings, all patients retained serviceable hearing and no facial nerve dysfunction was identi ed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Current strategies include observation with imaging, stereotactic radiosurgery (SRS), or microsurgical resection. While observation may be reserved for slow‐growing lesions, SRS could be offered to patients ineligible to undergo surgery, with moderate risks of radiation‐induced complications 3 . Microsurgical resection offers the possibility of gross total resection (GTR), 4 yet surgical access to the IAC and CPA requires invasive procedures.…”
Section: Introductionmentioning
confidence: 99%
“…While observation may be reserved for slow-growing lesions, SRS could be offered to patients ineligible to undergo surgery, with moderate risks of radiation-induced complications. 3 Microsurgical resection offers the possibility of gross total resection (GTR), 4 yet surgical access to the IAC and CPA requires invasive procedures. The middle fossa route approaches the pathology superiorly, while the retrosigmoid and translabyrinthine routes approach the pathology posteriorly.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Data regarding single-treatment SRS for VS with radiographic brainstem compression are limited and restricted to patients treated with Gamma Knife (GK). 5 A deficit in the literature is evaluation of the safety of treating VS with radiographic brainstem compression with a single-treatment SRS delivered through linear accelerator (linac). The purpose of this report is to fill this void by reporting outcomes in an unselected series of patients treated with a standardized approach at our institution.…”
mentioning
confidence: 99%
“…Data regarding single-treatment SRS for VS with radiographic brainstem compression are limited and restricted to patients treated with Gamma Knife (GK) 5 . A deficit in the literature is evaluation of the safety of treating VS with radiographic brainstem compression with a single-treatment SRS delivered through linear accelerator (linac).…”
mentioning
confidence: 99%